Employee engagement at a Lafarge Cement South Africa production facility - Buitendag, Sarel Johannes (University of the Free State, 2014)
Increased competition due to lower sales margins, excess capacity, imports and a new entrant into the local market has led to various attempts to improve competitiveness in the cement industry over the last few years. The contribution of employees to improve competitiveness and sustainability required the companies to ensure higher levels of employee engagement to fuel innovation and productivity. Lafarge SA recently experienced increases in employee turnover and negative operational performance, indicators of possible low engagement levels. The purpose of the study was to determine the engagement levels at Lafarge SA. This quantitative study used three measures, the Gallup Q12, Utrecht Work Engagement Scale (UWES) and Work Engagement Scale (WES), to determine the antecedents of engagement and the levels of psychological engagement at Lafarge SA. According to the Gallup Q12, the engagement level for Lafarge SA is 65.78%. The composite psychological engagement level according to the WES is 68.14%, and 64.84% according to the UWES. These levels are similar to the engagement level of other South African companies. The research has identified several antecedents to improve employee engagement at Lafarge SA. Employees have a desire for feedback and recognition as this assists in the employees’ feeling of adding value to the company. Lafarge SA has to develop employees, in line with their own talents. Decision making is a key driver to improve employee engagement. Management of Lafarge SA should create an environment that fosters the growth of a true social connection and mutual support at the company. Open, frequent, honest feedback on job performance contributes significantly to the employees’ perception of their worth and meaning. Effective training remains a challenge for organisations; managers should facilitate the process to enable employees to update their skills and ability to the benefit of the company. The research confirms the negative relationship between employees’ intention to stay and their levels of engagement. Organisational leadership should allow a two-way open communication environment, assisting further in creating a harmonious working environment where employees xi respect and help each other, and is committed to employee well-being. Employees should release their discretionary effort, be prepared for change, be positive, encouraging, helpful and accountable and, lastly, they should seize the opportunity to make things better for themselves and their organisation. Lafarge SA therefore needs to implement measurable organisational strategies to enhance employee engagement that will improve competitiveness and the retention of talent.
Dissertation (MBA (Business Administration)) --University of the Free State, 2014
Keywords: Employee engagement; Organisational culture; Organisational leadership; Gallup Q12; Utrecht work engagement scale; Work engagement scale; Cement industry; Lafarge, South Africa